Removal of methylene blue from dye effluent using ageratum conyzoide leaf powder (ACLP) - Ezechi, E.H. (American Institute of Physics Inc., 2015)
Methylene blue (MB), a common environmental pollutant discharged from dye effluents were removed from synthetic effluents in this study using ageratum conyzoide leaf powder. Effects of operating parameters such as pH, initial Methylene blue concentration, adsorbent weight and contact time were examined on methylene blue removal whereas stirring speed was constant at 100 rpm. Results show that low pH (3-4) had more Methylene blue removal than high pH. Methylene blue removal decreased when initial concentration was increased but increased when adsorbent weight was increased. Removal of Methylene blue by Ageratum conyzoide leaf powder was rapid and significantly above 80 in all initial concentrations examined. At optimum conditions of pH 3, 20 minutes contact time and adsorbent weight of 60 mg for Methylene blue initial concentration of 20 mg/L, 40 mg/L and 60 mg/L, Methylene blue removal of 84.7, 83.9 and 81.2 were obtained respectively. Results suggest that Ageratum conyzoide leaf powder could be potential adsorbents for Methylene blue removal from dye effluents. Â© 2015 AIP Publishing LLC.